In-situ Measurement of the Arctic Ocean for Optical Property Analysis During 2019 Cruise - Sungjae Lee; Hyun-Cheol Kim (Geo Data, 2020)
The Arctic issue has increased due to global warming. The Arctic is losing the role of cooling because reducing sea ice by warming on the Arctic, which is changing the energy balance on the Earth system. Change of Arctic ocean, atmosphere, and cryosphere influence on an ecosystem of Arctic as well. These changes are monitoring by remote sensing due to the Arctic is difficult for human access, and where is a wide area. However, a low solar altitude on the Arctic limits Ocean Color Algorithms applies to the Arctic because most ocean color algorithms are based on empirical data in the mid-latitude. Continuous data sampling on the Arctic ocean is the best way to improve and develop a suitable ocean color algorithm for the Arctic. This paper aims to report ocean observation data acquired by Ice-Breaker research vessel Araon during the summer Arctic expedition of 2019. Acquired samples are chlorophyll-a, suspended sediment concentration, in-situ measured ocean optical properties. Sampled data showed that there is a significant effect of dissolved organic matter in its inherent optical properties. We use these data for the aims of improving and develop ocean color algorithms in the Arctic.